Adenomatous Hyperplasia of Bowman's Capsule Epithelium in a Dog with Metastatic Nasal and Hepatic Neuroendocrine Carcinoma. (September 2022) - Machida, Yukino; Higo, Marika; Doge, So; Nagashima, Tomokazu; Kishimoto, Takuya E.; Yoshimura, Hisashi; Yamamoto, Masami; Okada, Kazuki; Yayoshi, Naoko; Hatakeyama, Hitoshi; Michishita, Masaki
Summary: A 12-year-old spayed Shiba dog with a nasal neuroendocrine carcinoma and multiple hepatic nodules was necropsied. Histologically, proliferated blast cells with a monolayer or multilayered structure were observed in the kidney. This blast cell proliferation extended from Bowman's capsule epithelium to the proximal tubule in approximately 3% of nephrons. Immunohistochemistry revealed that blast cells were positive for vimentin, Wilm's tumour protein 1 (WT1), paired box 2 (PAX2) and CD10, but negative for cytokeratin (CK) AE1/AE3, CK19, CAM5.2, synaptophysin and chromogranin A. On the basis of these findings, adenomatous hyperplasia of Bowman's capsule epithelium was diagnosed. Multiple yellowish‒white nodules (1–3 cm) were found in the liver and diagnosed as neuroendocrine carcinoma with metastases to the lungs, adrenal glands and pancreaticoduodenal lymph nodes. Graphical abstract: Image 1